Common-path diffraction optical tomography with a low-coherence illumination for reducing speckle noise - Park, HyunJoo (2015)
Common-path diffraction optical tomography (cDOT) is a non-invasive and label-free optical holographic technique for measuring both the three-dimensional refractive index (RI) tomograms and two-dimensional dynamic phase images of a sample. Due to common-path geometry, cDOT provides quantitative phase imaging with high phase sensitivity. However, the image quality of the cDOT suffers from speckle noise; the use of a monochromatic laser inevitably results in the formation of parasitic fringe patterns in measured quantitative phase images. Here, we present a technique to reduce speckle noise in the cDOT using a low-coherence illumination source. Utilizing a Ti-sapphire pulsed laser in the cDOT, we achieved the reduction of speckle noise in both the three-dimensional RI tomograms and two-dimensional dynamic phase images.